Speaking Activities in English Debating Club: a Case Study at English Conversation and Debating Club of SMKN 1 Pandeglang - Siti Suharsih; Yanna Supriatna (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
The purposes of the research is aimed at knowing how speaking activities and speaking difficulties are practiced in English Debating Club. The method used in this research was a case study. The instruments used to collect the data were observation, questionnaire, and interview. The respondents were 15 students of English Conversation and Debating Club at SMKN 1 Pandeglang. The result of the research confirms that by joining English Conversation and Debating club, students are able to (1) speak English fluently because they have more practice; (2) they can speak English quietly accurate; (3) the students are custom to speak English; and (4) they also speak with few grammatical errors, few long pauses, and only few clarifications for the beginners debaters (junior members) than the experienced debaters (senior members). On the other side, the difficulties of speaking found when they selecting the data and evidences, making argument, and making rebuttal due to the various resources.